Lifestyle Of Indonesian Education University Students During The Covid-19 Pandemic - Lilis Komariyah; Lucky Angkawidjaja Roring; Agus Gumilar; Burhan Hambali; Tri Martini; Tasya Aulia Rahma (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2021)
The purpose of this study was to obtain empirical data related to student lifestyle analysis at the Indonesia University of Education during the COVID-19 pandemic. The method that will be used in this research is descriptive. By creating a database related to student physical activity at the Indonesian Education University during the COVID-19 pandemic. The instrument that will be used in this research is an instrument developed by Douglas & Donna named Fantastic Lifestyle Assessment. The results of the analysis show that the lifestyle or lifestyle of students within the Indonesian Education University during the Covid-19 Pandemic showed poor results where out of a total of 274 respondents 38% were in the low category and there were even 2 respondents in the dangerous zone category, and only a total of 13% were in poor condition. ideal and 48% are in the sufficient category. The Covid-19 pandemic has greatly disrupted the stability of lifestyle conditions through the parameters measured, namely the condition of family and friends, physical activity, nutritional or nutritional intake, cigarette consumption, alcohol consumption, sleep quality and stress levels, personality, ability to understand events, and satisfaction with career.